Effects of histidine load on ammonia, amino acid, and adenine nucleotide concentrations in rats - Holeček, Milan; Vodeničarovová, Melita (Amino acids, 2019)
The unique capability of proton buffering is the rationale for using histidine (HIS) as a component of solutions for induction of cardiac arrest and myocardial protection in cardiac surgery. In humans, infusion of cardioplegic solution may increase blood plasma HIS from ~ 70 to ~ 21,000 µM. We examined the effects of a large intravenous dose of HIS on ammonia and amino acid concentrations and energy status of the body. Rats received 198 mM HIS intravenously (20 ml/kg) or vehicle. Samples of blood plasma, urine, liver, and soleus (SOL) and extensor digitorum longus (EDL) muscles were analysed at 2 or 24 h after treatment. At 2 h after HIS load, we found higher HIS concentration in all examined tissues, higher urea and ammonia concentrations in blood and urine, lower ATP content and higher AMP/ATP ratio in the liver and muscles, higher concentrations of almost all examined amino acids in urine, and lower glycine concentration in blood plasma, liver, and muscles when compared with controls. Changes in other amino acids were tissue dependent, markedly increased alanine and glutamate in the blood and the liver. At 24 h, the main findings were lower ATP concentrations in muscles, lower concentrations of branched-chain amino acids (BCAA; valine, leucine, and isoleucine) in blood plasma and muscles, and higher carnosine content in SOL when compared with controls. It is concluded that a load of large HIS dose results in increased ammonia levels and marked alterations in amino acid and energy metabolism. Pathogenesis is discussed in the article.
Keywords: adeninnukleotidy; Cardioplegic Solutions; Glutamine; Amino Acids; Ammonia; zvířata; Rats; Histidine; amoniak; mužské pohlaví; močovina; Carnosine; energetický metabolismus; Energy Metabolism; Organ Specificity; Myocardial protection; HTK solution; kardioplegické roztoky; Rats, Wistar; Branched-chain amino acids; karnosin; Ketoglutaric Acids; krysa rodu Rattus; intravenózní podání; aminokyseliny; Glycine; potkani Wistar; Ketoglutarate; Tetrahydrofolate; Adenine Nucleotides; orgánová specificita; Animals; kyseliny ketoglutarové; Tissue Distribution; ATP depletion; Urea; tkáňová distribuce; Administration, Intravenous; Male; histidin